2017
DOI: 10.1002/clen.201600825
|View full text |Cite
|
Sign up to set email alerts
|

Profiles and Risk Assessment of Heavy Metals in Great Rift Lakes, Kenya

Abstract: Heavy metal pollution in surface water of four lakes (Naivasha, Elementaita, Nakuru, and Bogoria) of the Great Rift Valley in Kenya, East Africa was investigated in this study. Eight heavy metals including chromium (Cr), nickel (Ni), copper (Cu), zinc (Zn), arsenic (As), lead (Pb), cadmium (Cd), and mercury (Hg) were determined using inductively coupled plasma-mass spectrometer (ICP-MS). Among the tested heavy metals, Cd and Hg were detected in all surface water samples. The concentrations of Cr, Cd, Ni, and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…15 These results are similar to those obtained in the Yangtze river in China, the Bangshi river in Dhaka, Bangladesh and the Great Rift Valley in Kenya. 47 , 55 , 56 The value obtained for As across all rivers raises carcinogenic concerns for the residents around these rivers. 57 Inorganic As is a known human carcinogen.…”
Section: Discussionmentioning
confidence: 99%
“…15 These results are similar to those obtained in the Yangtze river in China, the Bangshi river in Dhaka, Bangladesh and the Great Rift Valley in Kenya. 47 , 55 , 56 The value obtained for As across all rivers raises carcinogenic concerns for the residents around these rivers. 57 Inorganic As is a known human carcinogen.…”
Section: Discussionmentioning
confidence: 99%
“…The standard solutions were purchased from the CRM/RM information center of China and diluted using deionized water; mixed diluted solutions were used to obtain the standardization curves. More details for ICP-MS were reported previously [22]. The detection limits of heavy metals ranged between 1.1 × 10 −9 g/L and 12 × 10 −9 g/L for all heavy metals except Hg.…”
Section: Sample Analysismentioning
confidence: 96%
“…Heavy metals in water are a global concern due to their bioaccumulation, environmental hazards, and persistence (Goretti et al 2016;Chowdhury et al 2016). Heavy metals are released into lakes and other water bodies as a consequence of rapid population growth and anthropogenic activities, such as poorly treated industrial and domestic sewage and intensified agricultural runoff (Bhuiyan et al 2011;Islam et al 2015;Yang et al 2017). Industrial activities, for example electroplating, metal smelting, burning of fossil fuels, and chemical industry wastewater can release heavy metals such as As, Cu, and Pb (Bissen and Frimmel 2003;Zhang et al 2016;Noli and Tsamos 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies related to heavy metals have focused on industries, such as mining, agriculture such as irrigation of agricultural lands with sewage, and aquaculture (e.g., Rattan et al 2005;Noli and Tsamos 2016;Xia et al 2018). There are some studies that reported heavy metal pollution in some typical urban lakes (e.g., Li et al 2013;Yang et al 2017). However, little information is available on potential heavy metal pollution in lakes that are under rapid watershed urbanization, especially considering a large spatial gradient with a long linear distance and great variations in topographic relief.…”
Section: Introductionmentioning
confidence: 99%